Obtaining high-power ultra-wideband radio pulses with resonance shapers; Soviet Technical Physics Letters; Vol. 17, № 7 - Novikov S. A. Sergey Avtonomovich; Razin S. V.; Chumerin P. Yu.; Yushkov Y. G. Yuri Georgievich (1991, 1991)
В фонде НТБ ТПУ отсутствует